The Status of the Church in North America - Burdick, Brent H. (Review and expositor, 2018)
The number of Christians in American churches is declining rapidly, and the number of people in America who claim no faith is increasing. This article examines the current context and the challenges that the American Church faces, which include cultural influences, generational replacement, non-adaptive leadership, discipleship, training, and the loss of mission within the American Church., Despite the loss of numbers, the American Church still wields significant global influence owing to its missionary sending and exporting of media, marketing, and technological influence. The global Church follows the leadership of the American Church, for good or ill. Aspects of the Church that are exported, however, often reflect American cultural values rather than traditionally held biblical ideals. Understanding the dynamics, issues, peculiarities, flaws, and successes of the Church in America is therefore imperative if negative trends are ever able to be stemmed in the American Church, and if the American Church hopes to continue contributing significantly to global Christianity., The Church in North America has many expressions, and is extremely varied. Thousands of denominations have been formed over the years, reflecting every theological persuasion, episcopal and leadership structure, worship style, ethnic identity, and geographic area. This article explores the context in which the American Church functions, examines some of the factors and trends affecting the Church in America, discusses why there is reason for hope, and suggests some ways for the Church to move forward in uncertain times.